2011
DOI: 10.1038/nature10279
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for TCF-1 in T-lineage specification and differentiation

Abstract: The vertebrate thymus provides an inductive environment for T-cell development. Within the thymus, Notch signals are indispensable for imposing the T-cell fate on multipotential hematopoietic progenitors, but the downstream effectors that impart T-lineage specification and commitment are not well understood. Here we show that transcription factor, T-cell factor 1 (TCF-1), is a critical regulator in T-cell specification. TCF-1 is highly expressed in the earliest thymic progenitors, and its expression is upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
453
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(479 citation statements)
references
References 34 publications
23
453
1
2
Order By: Relevance
“…RBP-Jk deletion selectively decreased IL-22-producing NKp46 + IL-7Ra + ILCs in the lamina propria but not in the Peyer's patches (45). Epigenetic analysis revealed that IL-7Ra expression in ILC2 cells was directly regulated by TCF1, which was shown to be a direct target of the Notch-RBP-Jk pathway in T cells (46,47). In fact, we also found ICN1 binding on the promoter region (231 kb upstream from the TSS) of TCF1 in gd T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RBP-Jk deletion selectively decreased IL-22-producing NKp46 + IL-7Ra + ILCs in the lamina propria but not in the Peyer's patches (45). Epigenetic analysis revealed that IL-7Ra expression in ILC2 cells was directly regulated by TCF1, which was shown to be a direct target of the Notch-RBP-Jk pathway in T cells (46,47). In fact, we also found ICN1 binding on the promoter region (231 kb upstream from the TSS) of TCF1 in gd T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of TCF1/LEF1 have been well established in the thymus; they are indispensable in driving T-cell development (37). Nevertheless, their functions in the periphery remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the absence of the transcription factor TCF1 (Tcf7), whose deletion has been shown to result in loss of canonical Wnt signaling in DN4 thymocytes and mature T lymphocytes, 38,39 had no impact on the accumulation of ETPs and DN2s in the OP9-DW4 cocultures ( Figure 3D). Although TCF1 is crucial for early T-cell development, 26,40 compelling evidence suggests that TCF1 is not acting as an effector of canonical Wnt signaling in early T-cell development. 38,40 Wnt4 regulates TEC numbers during fetal thymopoiesis and postnatal thymic expansion Although our results indicate that Wnt4 has a direct effect on ETP and DN2 numbers, such an early defect would not be sufficient to explain a 2-fold difference in total cellularity because it should be compensated for at later stages.…”
Section: Wnt4 In Fetal and Postnatal Thymopoiesis 5167mentioning
confidence: 99%